A study on adverse effect following immunization COVID-19 vaccination Covishield among MBBS student s of a tertiary care institution in a rural area of Chhattisgarh, India - Alam, M. N.; Khatoon, Shagufta; Verma, Nirmal (International Journal Of Community Medicine And Public Health, 2021)
Background: India has granted emergency use authorization to two COVID-19 vaccines, Pune based Serum Institute of India’s Covishield and Hyderabad- based Bharat Biotech International Ltd.’s Covaxin, for the vaccination drive. Once a vaccine is in use, it must be continuously monitored to make sure it continues to be safe. These data will add on in policy making and also help vaccine to be safely tracked throughout its use. In view of above background present study has been conducted to determine adverse effect following immunization. Methods: A cross sectional observational study was conducted among 400 MBBS students of a rural medical college in Chhattisgarh, India from January 2021 to March 2021. Approval was taken from institutional ethical committee and written informed consent was obtained from participants. A semi-open questionnaire was used to estimate the adverse effect following Covishield administration. Data was processed, analysed using SPSS software and information was obtained. Results: Study shows most common adverse effect was pain at injection site (86%), followed by fever (76%). Female received more (69%) treatment compared to male (31%). Almost 100% of subject experienced adverse effect following immunization (AEFI) following first dose administration whereas about 20% only experienced adverse effect following administration of second dose. Conclusions: Pain at injection site was most common adverse effect followed by fever. Adverse effect was four times more with first dose compared to second dose. Female received more treatment compared to male. Majority had fever and pain for 1-2 days only. Thus, it was concluded that vaccine have no serious side effect.